Validity of measuring wheelchair kinematics using one inertial measurement unit during commonly used testing protocols in elite wheelchair court sports - Rupf, R.; Tsai, M. C.; Thomas, S. G.; Klimstra, M. (Journal of Biomechanics, 2021)
Wheelchair court sports can measure both continuous and discrete wheelchair kinematics using Inertial Measurement Units (IMU) during testing and games. A method involving three IMU (3IMU) shows good validity with motion capture systems, but the hardware cost and the need for multiple sensors may make it a barrier for implementation in a sport context. A method using only one wheel mounted IMU (1IMU) has been developed that may reduce this cost, but further validation is required. This study assessed the validity of 1IMU compared to 3IMU, across a variety of continuous and discrete measurements during common on-court testing protocols, using national team athletes. Subjects recruited from national Wheelchair Basketball and Wheelchair Rugby programs performed a series of sprint, agility, and pivot testing protocols. Continuous wheel speed, frame rotation, and wheelchair speed data as well as a number of important discrete metrics including peak linear and rotational speeds, were compared between 3IMU and 1IMU. Low error (RMSE < 0.15 m s-1) and high linearity (R2 > 0.99) were seen in continuous measurements for wheel speed. Similar observations were made for frame rotational speed (RMSE < 11° s-1 and R2 < 0.97) during continuous measurements. Good to excellent intraclass correlations (ICC) were observed for peak linear speeds (ICC > 0.86) and frame rotational speeds (ICC > 0.94). Overall, 1IMU offers a lower cost solution that provides valid information for pertinent outcomes in wheelchair sports to use in the field.